An Evaluation of Severe Plastic Deformation on the Densification Behaviour of Powder Metallurgy Aluminium Alloy Al-Mg-Si-Cu-Fe and Al-Zn-Mg-Cu - Bidulský, Róbert; Grande, Marco Actis; Bidulská, Jana; Kočiško, Róbert; Kvačkaj, Tibor (IntechOpen, 2011)
None